Fractal Evolution Characteristics on the Three-Dimensional Fractures in Coal Induced by CO2 Phase Transition Fracturing - Zhang, Zhen; Liu, Gaofeng; Lin, Jia; Barakos, George; Chang, Ping (MDPI, 2024)
To analyze the transformed effect of three-dimensional (3D) fracture in coal by CO2 phase transition fracturing (CO2 -PTF), the CO2 -PTF experiment under a fracturing pressure of 185 MPa was carried out. Computed Tomography (CT) scanning and fractal theory were used to analyze the 3D fracture structure parameters. The fractal evolution characteristics of the 3D fractures in coal induced by CO2 -PTF were analyzed. The results indicate that the CO2 phase transition fracturing coal has the fracture generation effect and fracture expansion-transformation effect, causing the maximum fracture length, fracture number, fracture volume and fracture surface area to be increased by 71.25%, 161.94%, 3970.88% and 1330.03%. The fractal dimension (DN) for fracture number increases from 2.3523 to 2.3668, and the fractal dimension (DV) for fracture volume increases from 2.8440 to 2.9040. The early dynamic high-pressure gas jet stage of CO2 -PTF coal influences the fracture generation effect and promotes the generation of 3D fractures with a length greater than 140 µm. The subsequent quasi-static high-pressure gas stage influences the fracture expansion-transformation effect, which promotes the expansion transformation of 3D fractures with a length of less than 140 µm. The 140 µm is the critical value for the fracture expansion-transformation effect and fracture generation effect. Five indicators are proposed to evaluate the 3D fracture evolution in coal caused by CO2 -PTF, which can provide theoretical and methodological references for the study of fracture evolution characteristics of other unconventional natural gas reservoirs and their reservoir stimulation.